NUMA-Aware Task Scheduling Strategy Aiming to Reduce Cache Conflicts - Nolasco, Thiago de Campos Ribeiro; Penna, Pedro Henrique; Freitas, Henrique Cota de (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2025)
This paper presents a NUMA-aware scheduling strategy that reduces cache conflicts by analyzing recent cache index access histories through cumulative distribution functions (CDF). The approach aims to minimize last-level cache (LLC) interference while maintaining load balance across CPUs. We developed a Rust-based simulator to evaluate the strategy under Zipf-distributed workloads, comparing it against the Distributed Intensity Online (DIO) strategy. Results show that the proposed method improves cache hit rates by up to 8.2%, reduces load imbalance up to 18%, and decreases tail latency by 14% relative to DIO. These improvements highlight the potential of fine-grained cacheoblivious scheduling strategies for real-world operating systems.